Analysis of Occupational Safety and Health (OSH) Risk Management in West Nusa Tenggara Province Using the HIRARC (Hazard Identification, Risk Assessment and Risk Control) and FMEA (Failure Mode and Effects Analysis) Methods - Bambang Heru Suharyadi; Ngudiyono; Ida Ayu Oka Suwati Sideman (Jurnal Locus Penelitian dan Pengabdian, 2026)
Due to the intensive use of labor, heavy equipment, and construction materials, construction projects pose high occupational safety and health (OSH) risks, raising the potential for workplace accidents and occupational diseases; therefore, this study aims to identify potential hazards and determine risk levels based on likelihood and severity using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) and FMEA (Failure Mode and Effects Analysis) methods. Data were collected through field observations, questionnaires, and interviews on two construction projects in Mataram. Risk assessment was conducted using a 5×5 risk matrix by evaluating Likelihood (L) and Severity (S), while FMEA was applied to prioritize risks using the Risk Priority Number (RPN). The results indicate that out of 50 work activities analyzed, 28 activities (56%) were categorized as medium risk, 13 activities (26%) as high risk, 7 activities (14%) as extreme risk, and 2 activities (4%) as low risk. High and extreme risks were predominantly associated with structural work, heavy equipment operations, and work at heights, which have inherently higher hazard exposure. These findings demonstrate that construction projects have significant OSH risk levels that require systematic and continuous risk management. The application of HIRARC and FMEA methods provides a structured and comprehensive approach for hazard identification, risk evaluation, and prioritization. Furthermore, applying risk controls based on the hierarchy elimination, substitution, engineering, administration, and PPE is essential to reduce risks to acceptable levels. Continuous improvement through better supervision, regular training, and consistent PPE use is necessary for a safer, healthier, and more productive workplace.